Comparison of Submucosal With Intramuscular or Intravenous Administration of Dexamethasone for Third Molar Surgeries: A Systematic Review and Meta-Analysis - Hou, Chengyu; Liu, Feng; Liu, Chengbin (Frontiers in Surgery, 2021)
Objective: The study aimed to review evidence on the efficacy of submucosal (SM) administration vs intravenous (IV) or intramuscular (IM) route of injections of dexamethasone for improving outcomes after mandibular third molar surgery. Methods: PubMed, Embase, CENTRAL, and Google Scholar were searched for randomized controlled trials (RCTs) up to 20th May 2021. Early (2-3 days) and late (7 days) outcomes were compared between SM vs IV or IM dexamethasone. Quality of evidence was assessed based on GRADE. Results: 13 trials were included in the systematic review and 10 in the meta-analysis. Meta-analysis indicated a significant reduction in early pain with IV dexamethasone but no such difference for late pain compared to the SM group. There was no difference in early and late swelling scores between the SM and IV groups. Pooled analysis indicated no significant difference in early and late trismus between SM and IV groups. Comparing SM with IM dexamethasone, there was no significant difference in early and late pain scores. Swelling in the early and late postoperative periods was not significantly different between the two groups. There was no significant difference in early and late trismus between SM and IM groups. The quality of evidence was low for all outcomes. Conclusion: Low-quality evidence suggests that SM infiltration of dexamethasone results in similar outcomes as compared to IV or IM administration of the drug after third molar surgeries. Further high-quality RCTs are needed to corroborate the current conclusions.